2021
DOI: 10.12965/jer.2142130.065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical exercise on cognitive function in older adults’ carriers versus noncarriers of apolipoprotein E4: systematic review and meta-analysis

Abstract: The presence of apolipoprotein (Apo) E4 is a genetic risk factor in cognitive impairment. Physical exercise contributes to slowing cognitive impairment in older adults, but little is known about the influence of exercise on ApoE4 carriers and noncarriers. The objective of systematic review is to study the role of physical exercise in older adults' ApoE4 carriers and noncarriers. A systematic literature search was carried out in five international databases: PubMed, Web of Science, PeDro, Scopus, and SPORTDiscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Physical activity has been shown to reduce Aβ accumulation, improve cholesterol levels, reduce neuroinflammation, and enhance cognitive function [ 246 ]. Despite some contradictory evidence in the field, it is becoming increasingly apparent that the beneficial effects of exercise and diet are likely dependent on APOE genotype [ 247 ]. Following the assessment of physical activity and cognitive function in 806 participants over 6 years, a recent study showed that an active lifestyle has a favorable correlation with cognitive performance in APOE4 non-carriers [ 248 ].…”
Section: Apoe-targeted Therapeutic Strategiesmentioning
confidence: 99%
“…Physical activity has been shown to reduce Aβ accumulation, improve cholesterol levels, reduce neuroinflammation, and enhance cognitive function [ 246 ]. Despite some contradictory evidence in the field, it is becoming increasingly apparent that the beneficial effects of exercise and diet are likely dependent on APOE genotype [ 247 ]. Following the assessment of physical activity and cognitive function in 806 participants over 6 years, a recent study showed that an active lifestyle has a favorable correlation with cognitive performance in APOE4 non-carriers [ 248 ].…”
Section: Apoe-targeted Therapeutic Strategiesmentioning
confidence: 99%
“…A national policy to support physical exercise at home seems essential in this context, especially for older adults [50]. Policies that address the improvement of unhealthy behaviors, as well as sleep quality and MH, are important during quarantine, with physical exercise as an effective and affordable non-pharmacological therapy option, of low cost and without side effects, to achieve this objective in an economical and sustainable way [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors may also interact with behavioral factors and affect cognitive function. The effect of physical exercise on cognitive performance in older adults is also conditioned or moderated by the presence of apolipoprotein E (ApoE4) [ 12 , 13 ], a genetic risk factor in cognitive impairment. Dietary habits such as protein or fiber intake showed a similar pattern [ 14 ].…”
Section: Introductionmentioning
confidence: 99%